2001
DOI: 10.1182/blood.v98.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial membrane sensitivity to depolarization in acute myeloblastic leukemia is associated with spontaneous in vitro apoptosis, wild-type TP53, and vicinal thiol/disulfide status

Abstract: Nonresponse to remission-induction chemotherapy, which remains a major problem in acute myeloblastic leukemia (AML), has been linked to cellular resistance to apoptosis. Because the apoptosis induced by chemotherapeutic drugs is mediated by loss of mitochondrial transmembrane potential (MTP), it was postulated that sensitivity to mitochondrial membrane depolarization might be heterogeneous in AML. Using the uncoupling agent carbonyl cyanide m-chlorophenylhydrazone (mClCCP), the mitochondrial membrane sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Mitochondrial depolarization has been shown to contribute to apoptosis in various cell types [46][47][48][49], including nitroprusside-treated PC12 cells [50]. However, the role of NGF and p53 in nitroprusside-induced mitochondrial depolarization is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial depolarization has been shown to contribute to apoptosis in various cell types [46][47][48][49], including nitroprusside-treated PC12 cells [50]. However, the role of NGF and p53 in nitroprusside-induced mitochondrial depolarization is not known.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, evidence implicating MAP kinase in Bcl-2 phosphorylation may be relevant (42). Finally, recent studies have demonstrated that induction of apoptosis by cytotoxic drugs in primary human leukemic blast specimens correlates closely with loss of ⌬⌿ m (43). It will clearly be of interest to determine whether MEK1/2 inhibitors increase ara-C-induced apoptosis in such cells, and if so, whether this event occurs independently of loss of ⌬⌿ m , as noted in HL-60 cells.…”
Section: Figmentioning
confidence: 95%
“…Firstly TG02 has efficacy against a broader range of primary samples than lestaurtinib. Secondly, the strong association between TG02 and lestaurtinib within the subgroup of samples with a FLT3-ITD suggests convergence on a common downstream apoptotic pathway, the consequences of which may depend on the differing intrinsic sensitivities of individual leukaemic clones to apoptosis (Pallis et al, 2001;Brunelle et al, 2009). For example, BCL2 over-expression is known to induce resistance to both CDK and FLT3 inhibitors (Dasmahapatra et al, 2006;Kohl et al, 2007).…”
Section: Discussionmentioning
confidence: 99%